1995
DOI: 10.1002/ana.410380507
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental effects of X monosomy: A volumetric imaging study

Abstract: Thirty girls with Turner syndrome (TuS) were compared with 30 individually age-matched controls on volumetric brain measures derived from magnetic resonance imaging and on measures of psychological functioning. As expected, girls with TuS performed more poorly on visual-spatial and intellectual measures relative to controls, and were rated by their parents as having more significant problems in attention and social behaviors. Although no group differences in overall cerebral or subcortical volumes were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 20 publications
6
84
1
1
Order By: Relevance
“…The SLF is a prominent white matter structure that extends in an arc above the insula from the frontal lobe to fan out into the parietal, occipital, and temporal lobes. Abnormal white matter within visuospatial pathways of the SLF is potentially consistent with volumetric studies of the parieto-occipital region in TS (Murphy et al, 1993;Reiss et al, 1995;Brown et al, 2002Brown et al, , 2004Molko et al, 2003). Functional imaging studies have shown that regions located within this pathway contribute to visuospatial processing.…”
Section: Frontoparietal and Parieto-occipital Pathwayssupporting
confidence: 68%
See 1 more Smart Citation
“…The SLF is a prominent white matter structure that extends in an arc above the insula from the frontal lobe to fan out into the parietal, occipital, and temporal lobes. Abnormal white matter within visuospatial pathways of the SLF is potentially consistent with volumetric studies of the parieto-occipital region in TS (Murphy et al, 1993;Reiss et al, 1995;Brown et al, 2002Brown et al, , 2004Molko et al, 2003). Functional imaging studies have shown that regions located within this pathway contribute to visuospatial processing.…”
Section: Frontoparietal and Parieto-occipital Pathwayssupporting
confidence: 68%
“…Complementing the findings of atypical cerebral functioning seen in fMRI studies, neuroanatomic studies of TS have consistently found decreased gray matter volume in the bilateral parietal lobes, parieto-occipital region, and subcortical gray matter (Murphy et al, 1993;Reiss et al, 1995;Brown et al, 2002;Good et al, 2003;Kesler et al, 2003;Molko et al, 2003), as well as increased volume of the superior temporal gyrus (STG) (Kesler et al, 2003), amygdala (Kesler et al, 2004a,b), and orbitofrontal cortex (Good et al, 2003). Recent volumetric MRI localized parietal lobe findings to the bilateral superior parietal lobule and postcentral gyrus (Brown et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…A positron emission tomography study of five adult women demonstrated a glucose hypometabolism in bilateral parietal and occipital regions (Clark, Klonoff, & Hadyen, 1990). Two anatomical MR studies, one with 18 and the other with 30 affected women, demonstrated bilateral reductions in parieto-occipital brain volume, together with other subcortical regions (Murphy et al, 1993; see also Reiss et al, 1993;Reiss, Mazzocco, Greenlaw, Freund, & Ross, 1995). Interestingly, the phenotype of Turner syndrome can differ depending on whether the remaining X chromosome is of paternal or maternal origin (Xm or Xp subtypes; Bishop, Canning, Elgar, Morris, Jacobs, & Skuse, 2000;Skuse, 2000;Skuse et al, 1997).…”
Section: Developmental Dyscalculia and The Ontogeny Of Number Represementioning
confidence: 99%
“…A positron emission tomography study of five adult women demonstrated a glucose hypometabolism in bilateral parietal and occipital regions (Clark, Klonoff, & Hadyen, 1990). Two anatomical MR studies also demonstrated bilateral reductions in parieto-occipital brain volume, together with several other cortical and subcortical regions (Murphy et al, 1993;Reiss et al, 1993;Reiss, Mazzocco, Greenlaw, Freund, & Ross, 1995).…”
Section: Introductionmentioning
confidence: 98%